PENGARUH KEPEMIMPINAN KEPALA DESA DAN KESADARAN MASYARAKAT TERHADAP KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (Studi Kasus Pada Kelurahan Desa Permanu Kecamatan Pakisaji Kabupaten Malang) - Sindi Kurniawati; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The purpose of this study was to determine the influence of village head leadership, public awareness of community compliance in paying land and building taxes. The research method used is quantitative research with published data collection techniques such as 5 to people who are taxpayers on land and buildings in Permanu Village, Pakisaji District, Malang Regency and for data analysis methods using multiple linear regression. In this study using a sample of 97 based on calculations using the Slovin formula. From the results obtained, researchers can prove that there is a simultaneous and simultaneous influence between the leadership of the village head, public awareness of community compliance in paying land and building taxes in Permanu Village, Pakisaji District, Malang Regency. Keywords: Village Head Leadership, and Community Awareness, Community Compliance.